EMERGENCY THORACOCENTESIS FOR HAEMOTHORAX DUE TO MESOTHELIOMA IN A DOG - Rajat Sagare; H. Vijaykumar; M. Chandrasekar; P. Pothiappan; S. Kavitha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A nine year old non-descript male dog was presented to Madras Veterinary College Teaching Hospital with a history of anorexia, weakness, and clinical signs of respiratory distress and pyrexia. TFAST (thoracic-focused assessment with sonography for trauma) of the lung was performed to rule out pleural effusion. Upon confirmation of pleural effusion, thoracocentesis was performed and sample was collected to identify the cause. The pleural effusion was confirmed as haemothorax and cytology of the sample was confirmed as mesothelioma.